Development and characterization of elastic nanocomposites for craniofacial contraction osteogenesis. Issue 2 (5th June 2014) - Levi‐Polyachenko, Nicole; Rosenbalm, Tabitha; Kuthirummal, Narayanan; Shelton, Julie; Hardin, Worth; Teruel, Maria; Hobley, Eboni; Wang, Rui; Day, Cynthia; Narayanan, Vishnu; David, Lisa; Wagner, William D.
Abstract Development of resorbable elastic composites as an alternative means to apply contractive forces for manipulating craniofacial bones is described herein. Composites made from the biodegradable elastomer, poly (1, 8‐octanediol co‐citric acid) (POC), and hydroxyapatite (nHA) with a 200 nm diameter (0–20% loadings) were created to develop a material capable of applying continuous contractive forces. The composites were evaluated for variation in their mechanical properties, rate of degradation, and interaction of the hydroxyapatite nanoparticles with the polymer chains. First, an ex vivo porcine model of cleft palate was used to determine the rate of cleft closure with applied force. The closure rate was found to be 0.505 mm N−1. From this approximation, the ideal maximum load was calculated to be 19.82 N, and the elastic modulus calculated to be 1.98 MPa. The addition of nHA strengthens POC, but also reduces the degradation time by 45%, for 3% nHA loading, compared to POC without nHA. X‐ray diffraction data indicates that the addition of nHA to amorphous POC results in the formation of a semicrystalline phase of the POC adjacent to the nHA crystals. Based on the data, we conclude that amongst the 0–20% nHA loadings, a 3% loading of nHA in POC may be an ideal material (1.21 MPa elastic modulus and 13.17 N maximum load) to induce contraction forces capable of facilitating osteogenesis and craniofacial bone repair. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 407–416, 2015.